2006
DOI: 10.1007/s00701-006-0777-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of arachnoid plasty using fibrin glue membrane after clipping of ruptured aneurysm on the occurrence of complications and outcome in the elderly patients

Abstract: Arachnoid plasty using fibrin glue is suggested to be effective in preventing complications associated with SAH and aneurysmal surgery. A better outcome in the elderly patients can be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…There are reports indicating that "arachnoid plasty" can reduce postoperarive SFC (6,15,16). We did not perform any arachnoid plasty, which may be effective in preventing postoperative CSDH.…”
Section: Peer-review Reportsmentioning
confidence: 84%
“…There are reports indicating that "arachnoid plasty" can reduce postoperarive SFC (6,15,16). We did not perform any arachnoid plasty, which may be effective in preventing postoperative CSDH.…”
Section: Peer-review Reportsmentioning
confidence: 84%
“…6,11,13) These materials are thought to be effective in preventing not only liquorrhea, but also postoperative subdural hygroma following arachnoid plasty. 6,7,11,13,14) However, several allergic reactions have been reported due to hypersensitivity to aprotinin. 2,5,7,12,15,16) These findings should be more widely known.…”
Section: Discussionmentioning
confidence: 99%
“…4) Thereafter, several studies have reported the application of fibrin glue placement methods in covering unfolded sylvian fissures, so preventing postoperative subdural hygroma and contributing to the improvement of clinical outcomes in aged patients. 6,7,11,13,14) Currently, this manipulation is widely accepted as an excellent option in arachnoid plasty. Arachnoid plasty with only fibrin sealant, 6,13) and combined with collagen sheets 7,14) or gelatin sponges 10) has been reported.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations